The Afdhaliyah Worship in organizing the Pilgrimage - Ilyas, Musyfikah (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2022)
This study discusses the afdhaliyah worship as a phenomenon in conducting the pilgrimage. The pilgrimage requires special physical and spiritual abilities, as well as having comprehensive and well organized knowledge so the implementation of the pilgrimage process ends with mabrur level. The research method uses a qualitative design by collecting data in a literature review, archive study, mass media, conducting in-depth interviews. Then processing and analyzing the data afterwards. The implementation of the pilgrimage includes worship that is carried out at a certain time, nuance, and place which based on the scholars' view is very essential to carry out; This worship is said to be afdhaliyah because it is very important to do, but in practice there are some people who really force themselves and even disobey the rules that have been set so that it can harm the implementation of the Hajj in general, and disregard the safety, benefit and security of the pilgrims in particular. This is interesting because the Hajj pilgrims are too pursuing profits rather than the safety and security of their individual with the result that many pilgrims experience heat stroke or heatstroke and heat exhaustion or fatigue which can trigger other diseases so that the pilgrims must receive more intensive care, this becomes a phenomena in the pilgrimage that must be observed and identified so that pilgrims should have not only pursued rewards, they also have to maintain their safety and security as well. In the implementation of the pilgrimage, it is necessary to carry out the obligatory and pillars of the pilgrimage itself as a condition for the pilgrimage validity. Afdhaliyah worship is valuable to do if the place is in the right conditions, on the other hand if it is dangerous for the life of the pilgrims then it is not allowed. Keywords: Worship, Hajj, Afdhaliyah